Latent Tariff Gains or Losses in Food and Live Animals Trade by ECOWAS Sub-Regional Members - D. M. Nyajo; G. O. Onogwu; G. Bulus (Journal of Multidisciplinary Science: MIKAILALSYS, 2025)
This study evaluates latent tariff gains and losses in the trade of food and live animals among ECOWAS member states from 2008 to 2023, with an emphasis on assessing the effectiveness of regional trade liberalization policies. The primary objectives include estimating export and import volumes, analyzing net trade balances, and identifying disparities in trade performance across member countries. Secondary data were sourced from the UN Comtrade database and analyzed using descriptive statistics and net trade analysis. The findings reveal marked disparities in intra-regional trade, with Côte d’Ivoire, Nigeria, and Senegal emerging as dominant exporters, while countries such as Guinea-Bissau and Liberia displayed limited engagement. Export volumes peaked at 1.67 billion USD in 2017, experienced a decline during the COVID-19 pandemic (950 million USD in 2020), and subsequently began to recover. Net trade performance varied significantly; Côte d’Ivoire and Senegal consistently posted surpluses (e.g., +137 million USD for Côte d’Ivoire in 2018), whereas Burkina Faso and Niger reported persistent deficits (e.g., -49 million USD for Burkina Faso in 2021). These results underscore structural imbalances in trade flows and point to the need for coordinated policy measures aimed at reducing non-tariff barriers, enhancing trade facilitation, and supporting less competitive economies within the region. While ECOWAS has made progress toward regional integration through trade liberalization, the realization of equitable economic participation demands targeted strategies to address persistent disparities and external vulnerabilities. Further research should examine the influence of political instability and international trade agreements on regional trade dynamics.